Characteristics of methadone-related fatalities in Norway. (November 2015) - Bernard, Jean-Paul; Khiabani, Hassan Z.; Hilberg, Thor; Karinen, Ritva; Slørdal, Lars; Waal, Helge; Mørland, Jørg
Abstract: There are currently over 7000 patients enrolled in opioid maintenance treatment (OMT) programs in Norway. A rise in methadone-related deaths proportional to increasing methadone sales over the period 2000–2006 has been observed, but the causative factors for these fatalities have been elusive. In the present study, individual characteristics, methadone concentrations and additional toxicological findings were analyzed. Methadone intoxication deaths (n = 264) were divided into 3 groups according to toxicological findings in whole blood: group 1 – methadone detected alone, or together with one additional drug at low or therapeutic levels, or a low concentration of ethanol (<1 g/L) (n = 21); group 2 – multiple additional drugs/substances detected below lethal levels (n = 175); group 3 – one or more additional drugs/substances detected at lethal levels, or ethanol >3 g/L (n = 55). Methadone blood concentrations in decedents who had been enrolled in OMT were higher than for decedents not in treatment, in all groups. Blood methadone concentrations around 1 mg/L were present in fatal multi-drug intoxications in OMT patients. Results suggest that some patients may be at risk of dying when combining therapeutic concentrations of methadone with other psychoactive substances. Somatic disease was a common finding among deceased OMT patients. Concentrations in methadone users not enrolled in OMT were predominantly between 0.3 and 0.4 mg/L and were not related to the presence of other drugs. However, methadone concentrations below 0.1 mg/L may be associated with intoxication following methadone use, both alone and in combination with other drugs. Younger male users (mean age 34 years) seemed to have a higher susceptibility to methadone intoxication. Highlights: 82% of decedents had used diverted methadone before death. Methadone was most often detected in addition to multiple drugs below lethal levels. Decedents with no relation to OMT were younger than decedents prescribed methadone. Methadone concentrations were not influenced by additional toxicological findings.